Varicella-zoster virus encephalitis in an AIDS patient - Toledo,P.V. (2004)
A 37-year-old man with a three-year history of Acquired Immunodeficiency Syndrome was admitted with impaired consciousness, seizures and fever. He was on highly active antiretroviral therapy and on neurotoxoplasmosis secondary prophylaxis. Laboratory exams from two months before showed a CD4 cell count of 37/µL and a viral load of 230,000 copies/mL. Three months before admission he developed herpetic skin rash in the right trunk and acyclovir was added to his treatment regimen. On physical exam he was drowsy and had motor and sensory aphasia. The patient had elevated protein levels and normal pressure in the cerebrospinal fluid (CSF). Contrast enhanced computed tomography scan of the brain showed a hypodense lesion in the left parietal lobe, with poorly defined margins and no contrast enhancement. The magnetic resonance scan (MRI) showed multiple hyperintensities in T2-weighted image in white and grey matters and hypointense products of hemorrhage in both hemispheres and in the cerebellum. He was empirically treated with intravenous acyclovir and prednisone. Viral DNA of Varicella-zoster virus (VZV) was detected in the CSF by means of polymerase chain reaction (PCR) analysis. Acyclovir was continued for 10 days and the patient became well, with improvement of aphasia.We present a case of VZV encephalitis, confirmed by nested PCR, in a patient with suggestive MRI findings, who succeeded with treatment. VZV encephalitis is a rare opportunistic infection, occurring in 0.1 to 4% of AIDS patients with neurological disease; it is related to severe immunodeficiency and has a high mortality.